Misresponse to Reversed and Negated Items in Surveys: A Review - Weijters, Bert; Baumgartner, Hans (Journal of Marketing Research, 2012)
There are important advantages to including reversed items in questionnaires (e.g., control of acquiescence, disruption of nonsubstantive responding, better coverage of the domain of content of a construct), but reversed items can also lead to measurement problems (e.g., low measure reliability, complex factor structures). The authors advocate the continued use of reversed items in measurement instruments but also argue that they should be used with caution. To help researchers improve their scale construction practices, the authors provide a comprehensive review of the literature on reversed and negated items and offer recommendations about their use in questionnaires. The theoretical discussion is supplemented with data on 1330 items from measurement scales that have appeared in Journal of Marketing Research and Journal of Consumer Research.